2022
DOI: 10.3389/fphar.2022.949745
|View full text |Cite
|
Sign up to set email alerts
|

Significant metabolic alterations in non-small cell lung cancer patients by epidermal growth factor receptor-targeted therapy and PD-1/PD-L1 immunotherapy

Abstract: Background: Cancer-related deaths are primarily attributable to lung cancer, of which non-small cell lung cancer (NSCLC) is the most common type. Molecular targeting therapy and antitumor immunotherapy have both made great strides in the treatment of NSCLC, but their underlying mechanisms remain unclear, especially from a metabolic perspective.Methods: Herein, we used a nontargeted metabolomics approach based on liquid chromatography-mass spectrometry to analyze the metabolic response of NSCLC patients to epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Another reported that oleic acid regulates inflammation, as well as various immunomodulators, through Th2/GATA-3 and interleukin-17/RORγt [ 48 ]. Inhibition of PD-L1, EGFR, and tyrosine kinases by palmitic acid has been reported [ 49 ]. Although fatty acids are commonly used in nano-emulsions, we showed that a derivative of palmitic acid improved T cell immune responses by inhibiting PD-L1 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another reported that oleic acid regulates inflammation, as well as various immunomodulators, through Th2/GATA-3 and interleukin-17/RORγt [ 48 ]. Inhibition of PD-L1, EGFR, and tyrosine kinases by palmitic acid has been reported [ 49 ]. Although fatty acids are commonly used in nano-emulsions, we showed that a derivative of palmitic acid improved T cell immune responses by inhibiting PD-L1 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase was composed of 0.1% formic acid in water (solvent A) and 0.1% formic acid in acetonitrile (solvent B), the flow rate was 0.30 mL/min and the column temperature was 30°C. The UPLC-MS/MS analytical conditions were as previously described ( 18 ). For MS, both positive and negative electrospray ionization (ESI) modes were used.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis was performed as previously described ( 18 ). Principal component analysis and partial least square discriminant analysis (PLS-DA) were used to investigate data clustering trends and differences among the groups.…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory and immune microenvironments induced by BLI are closely associated to the development and progression of NSCLC (Takada et al, 2022;Tang et al, 2023). Immunotherapy has made significant strides in the treatment of NSCLC in recent years, particularly with ICIs represented by inhibitors of the programmed cell death protein 1 (PD-1)/programmed cell death protein ligand 1 (PD-L1) pathway, which have substantially enhanced NSCLC patients' survival and prognosis (Yan et al, 2022;You et al, 2023). However, a substantial number of patients do not benefit from ICIs, and there is a risk of adverse effects related to immunotherapy, especially the incidence of checkpoint inhibitor-related pneumonia (CIP) in NSCLC patients, which is significantly higher than in patients with other types of tumors (Suresh et al, 2019;Cao et al, 2022c).…”
Section: Introductionmentioning
confidence: 99%